2011
DOI: 10.1111/j.1469-8137.2011.03752.x
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal‐like fungi in Carboniferous arborescent lycopsids

Abstract: Arbuscular mycorrhizal (AM)-like fungi in stigmarian appendagesStructurally preserved stigmarian appendages containing an AM-like endophytic fungus have been discovered in thinsection preparations of coal ball material from the Carboniferous of Great Britain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Recent studies have built on this foundation of knowledge and have shed fresh light on physiological mechanism controlling their development, structure, and interaction with other organisms (63)(64)(65)(66). The discovery that stigmarian rootlets were highly branched, developed root hairs and share the same branching architecture as extant Isoetes rootlets reveals a remarkable conservatism in rootlet architecture between the first giant trees and their only living herbaceous relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have built on this foundation of knowledge and have shed fresh light on physiological mechanism controlling their development, structure, and interaction with other organisms (63)(64)(65)(66). The discovery that stigmarian rootlets were highly branched, developed root hairs and share the same branching architecture as extant Isoetes rootlets reveals a remarkable conservatism in rootlet architecture between the first giant trees and their only living herbaceous relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Krings et al (2011) reported an AM-like fungus in the root system of an arborescent clubmoss from the latter part of the Carboniferous Period (315 million years ago). These plants bore an extensive root system with a unique evolutionary history.…”
Section: Fungal Partnershipsmentioning
confidence: 99%
“…However, some liverworts host fungal glomeralean endophytes (Chambers et al, 1999;Davis et al, 2003) that probably serve mutualistic rather than parasitic roles. Similarly, some modern lycopods host glomeralean endophytes (Read et al, 2000;Winther and Friedman, 2007) that form associations extending deep into the Paleozoic permineralized record Krings et al, 2005;Krings et al, 2007;Krings et al, 2011). Like lycopods, horsetails possess few diseases (Freeberg, 1962), except for a variety of maladies that affect silica metabolism (Ellis and Ellis, 1985;Quarles, 1995;Epstein, 1999), and especially bacterioses that are induced by strains of Pseudomonas syringae that afflict wheat and secondarily target Equisetum (Pasichnik et al, 2012).…”
Section: Can Plant Diseases Be Recognized In the Preangiospermous Fosmentioning
confidence: 99%
“…A difficulty in interpreting the presence of a fungal or other potential pathogen within host tissues is that the host likely was dead when it was preserved, and was exposed to the effects of non-pathogenic, saprophytic organisms. In addition, while alive, the plant may have hosted endophytic fungi that did not elicit a disease response (Krings et al, 2009(Krings et al, , 2011 and cannot be considered unequivocally as having been pathogenic, despite its presence within the tissues of the plant. Only the clear presence of a host reaction to an invading organism, or the presence of specialized hyphae such as haustoria that are known to be adaptations of an obligately biotrophic mode of life, are considered here to be adequate evidence for an observed pathogenic interaction.…”
Section: An Overview Of Pathogens In the Permineralized Fossil Recordmentioning
confidence: 99%